Controls, procedures, and risk - Loader, David (Burlington, MA : Butterworth-Heinemann, 2002)
"Controls, Procedures and Risk: covers the skills and procedures needed to enable effective monitoring and managing of risk, with case studies used to demonstrate 'success' and 'failure'; explains about procedures design, implementation and documentation and illustrates the solutions; and demonstrates the key controls and the importance of control functions, audit and risk management groups and policy."--BOOK JACKET.
Includes index.
opc 27/10/16
Loans
Keywords: Financial services industry - management; Operational risks and controls; Risk management